2019
DOI: 10.1021/acs.jpcb.9b01018
|View full text |Cite
|
Sign up to set email alerts
|

CoSIMS: An Optimized Trajectory-Based Collision Simulator for Ion Mobility Spectrometry

Abstract: A new, multi-threaded, trajectory method based software platform, CoSIMS, is revealed and compared to reference MOBCAL collision cross sections (CCS). CoSIMS employs various molecular mechanics algorithms to lessen the computational resources required to simulate thousands of buffer gas-ion collisions, including the neglect of London dispersion interactions at long distances and the removal of trajectories that insignificantly contribute to the total CCS via an ellipsoidal projection approximation. The showcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…This conformation corresponds to the position at (PC-1, PC-2) = (0.5, 0.45), where only AMBER12:EHT exhibited PMF ≈ 1.7 kcal/mol and the other force fields have PMF > 2.5 kcal/mol using our bulk solvent simulations (Figure a and Figure S3), which is completely different from the one we found at (PC-1, PC-2) = (1.4, 0.0) that contains the same two cis isomers. Here, the CCSs were also calculated by the CoSIMS program for the ensembles at T = 300 K, although we could not obtain CCS = 271 Å 2 that corresponds to the bent conformation reported by Gray et al Rather, a bent-twisted conformer comprising only 9–10 cis ( C in Figure b) might be a candidate for a minor conformation employing the McMD simulations, as discussed above. Another CCS study by Hyung et al revealed the bimodal distributions at 272 and 278 Å 2 via solvent-free replica exchange MD, whereas the three modal distributions at 283, 295, and 315 Å 2 were determined by our simulation in CHCl 3 using ff03 (see Figure S10a).…”
Section: Resultsmentioning
confidence: 87%
“…This conformation corresponds to the position at (PC-1, PC-2) = (0.5, 0.45), where only AMBER12:EHT exhibited PMF ≈ 1.7 kcal/mol and the other force fields have PMF > 2.5 kcal/mol using our bulk solvent simulations (Figure a and Figure S3), which is completely different from the one we found at (PC-1, PC-2) = (1.4, 0.0) that contains the same two cis isomers. Here, the CCSs were also calculated by the CoSIMS program for the ensembles at T = 300 K, although we could not obtain CCS = 271 Å 2 that corresponds to the bent conformation reported by Gray et al Rather, a bent-twisted conformer comprising only 9–10 cis ( C in Figure b) might be a candidate for a minor conformation employing the McMD simulations, as discussed above. Another CCS study by Hyung et al revealed the bimodal distributions at 272 and 278 Å 2 via solvent-free replica exchange MD, whereas the three modal distributions at 283, 295, and 315 Å 2 were determined by our simulation in CHCl 3 using ff03 (see Figure S10a).…”
Section: Resultsmentioning
confidence: 87%
“…One possibility is to combine the PES with additional experimental techniques, such as Raman spectroscopies to identify the vibrational modes responsible for the reorganization. [82] We propose that useful information can be reached even without additional experiments assuming that the water solvent response is dominated by librational motion.…”
Section: Discussionmentioning
confidence: 99%
“…The collisional cross-section values were computed using the CoSIMS code . The smFRET efficiency (FE), defined as (where Ro is the Förster distance and r the Cα-Cα distance), was computed using the ISDB module within the PLUMED driver .…”
Section: Methodsmentioning
confidence: 99%
“…The collisional cross-section values were computed using the CoSIMS code. 31 The smFRET efficiency (FE), defined as…”
Section: ■ Introductionmentioning
confidence: 98%